A Large Cystic Phyllodes Tumor of the Prostate - Chung, Hyun Chul; Lee, Hyo Serk; Kim, Tae Im; Kim, Dae Il; Park, Kwang Hwa; Song, Jae Mann (Yonsei medical journal, 2009)
We report a 65 year-old man with a large cystic phyllodes tumor of the prostate. The patient complained of abdominal discomfort and had a soft palpable mass. Computer tomography showed a solid and cystic mass in the pelvic fossa; the mass was adjacent only to the prostate. We excised the mass. Microscopic findings of the mass showed hyperplastic epithelium lined cysts with leaf-like intraluminal epithelia lined stromal projections, less than 2 mitotic counts/10 HPF, low-to-moderated cellularity, and mild-to-moderate cytoplasm atypia. The pathological findings were consistent with a phyllodes tumor of the prostate, a low-grade tumor. Twenty-eight months after the operation, the patient was well with no recurrence or metastases.